MODELING CONFINED PRESSURE CHANGES INDUCING ANOMALOUS ELECTROMAGNETIC FIELDS RELATED WITH EARTHQUAKES - Fujinawa Y.; Matsumoto T.; Takahashi K. (My University, 2002)
Electromagnetic field anomalies provide a means to estimate the confined water pressure changes through electrokinetic effects in the preparatory stages of an earthquake occurrence process. Typical shorter period pulse-like signals in the ULF band associated with seismic swarms (e.g., Fujinawa et al. [Phys. Chem. Earth (2000)]) are used to estimate the evolution of confined pressure changes based on a transient electrokinetic model. A model calculation using a simple conductivity structure indicates that the water pressure increases abruptly by several megapascals. It is indicated that sharper signals are observed at points less than a few kilometers from the source.